(untitled) (Iter, 2022)
The first Chilean novel can be found in the body ofan unpublished Chilean chronicle from the XVIIth century. It is a Baroque narrative which tells about a love relationship between two Mapuche youngsters. In this novel, the author often stops his narrative to make roomfor a number of quotations from Latín authors, mainly Ovid and Virgil. Curiously enough, however, these quotations aren’t but recompositions or “pasticci” of verses which are originally separated in the literary work they come from. This quotations, neverthelessy regularly make coherent and clearly meaningful texis. This paper attempts to analyze and explain this particular way ofwriting.